Sintesis Nanokitosan Dengan Metode Gelasi Ionik Menggunakan Pelarut Asam Asetat Dengan Variasi Konsentrasi Kitosan - Qonitannisa, Shofi; Fadli, Ahmad; Sunarno, Sunarno (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Nanochitosan research continues to be developed using easy and simple methods. The content of chitosan in shrimp shells is used as raw material for the synthesis of nanochitosan. The purpose of this study was to determine the effect of variations in the concentration of chitosan on the size of the nanochitosan produced using the Particle Size Analyzer (PSA) analysis method. The research was carried out through several stages including preparation of raw materials, manufacturing of chitosan, preparation of nanochitosan using the ionic gelation method and characterization of nanochitosan. The procedure for making nanochitosan is to make 1% acetic acid solution and 0.1% natrium tripolyphosphate (NaTPP). Chitosan solution with a concentration of 0.1% and 0.3% was stirred using a magnetic stirrer. After 15 minutes NaTPP solution added at a volume ratio of chitosan and NaTPP was 7:1. Stirring continuously for 1 hour at 1200 rpm. Furthermore, the characterization was carried out on the nanochitosan. The deacetylation degree of chitosan from dried shrimp industrial waste in the results of this study has met the quality standard of chitosan, namely 76.3%. The results of the research that have been carried out obtained the size of chitosan nanoparticles of 852.1 nm and 2591.4 nm. The polydispersity index of each concentration results 0.353 and 0.741. The higher chitosan concentration used, the higher of nanoparticle size and the polydispersity index results. Keywords: acetic acid, degree of deacetylation, ionic gelation, nanochitosan, natrium tripolyphosphate